Do rural youth want to stay rural? Influences on residential aspirations of youth in forest-located communities. Issue 5 (20th October 2022) - Bernsen, Nicole R.; Crandall, Mindy S.; Leahy, Jessica E.; Abrams, Jesse B.; Colocousis, Chris R.
ABSTRACT: Economic transitions have a wide variety of impacts on rural forest-located communities. Uncertain employment prospects and a lack of local higher education institutions may increase out-migration, while individual connections to the local natural environment and community itself may bind youth to their community of origin. We analyzed over 2, 000 survey responses from middle and high school youth from traditionally forest-dependent communities in greater Piscataquis County, Maine, and Coos County, Oregon (USA). We explored the role of school and community perceptions, place attachment, and educational aspirations in students' desired future residential location (rural or non-rural). Community perceptions and place attachment were positively related to desired future rural residence, while educational aspirations were negatively related. We conclude that rural forest-located communities may better retain or attract rural youth by focusing on community attributes and connections to the outdoors for continued community sustainability.